SOCIAL CAPITAL AND PARTICIPATION IN VIRTUAL STUDENT COMMUNITIES - Tsvetkova, Nikolina; Mavrodieva, Ivanka (PEOPLE: International Journal of Social Sciences, 2018)
Students nowadays participate in a number of virtual communities during their studies. They predominantly use social networks as a tool for organization and mobilization in connection with their education, however, they do not exploit the potential of their social networks to become learning networks well enough. Most often, students display a sense of affiliation to virtual student communities but their abilities to actively participate in collaborative virtual groups need enhancing. Their competences to create e-content are underdeveloped and they have to move forward from liking, through sharing and rewriting to generating genuinely own material on subjects from their studies. In addition, students’ communicative roles are mostly on the passive end of the continuum – those of a “lurker” or a receiver of knowledge and information rather than that of being active agents in virtual communication processes. Although they are able to identify the necessary sources and relevant content, they lack the capability to critically evaluate, select and transform it in order to achieve sustainable learning results which can subsequently be applied to contexts close to their future careers. The paper focuses in on a survey conducted among BA students from Sofia University at the beginning of 2018, which aimed at establishing the level of social maturity and social competences in connection with their learning and future professional realisation.